Strategies used to assess the quality of nursing care: Integrative Review (Research, Society and Development, 2021)
The evaluation of the quality of nursing care is one of the main components that allow the manager to identify the weaknesses of the work process and make decisions. The aim of this study was to present scientific evidence on the strategies used to assess the quality of nursing care in the hospital context. The work was carried out according to the protocol established and recommended by the Joanna Briggs Institute: 1) Formulation of the research question; 2) specification of study selection methods; 3) data extraction procedure; 4) critical analysis and evaluation of the included studies 5) data extraction and 6) presentation of the integrative review of the knowledge produced / published and conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes methodology. It was observed that there was no increase in the number of publications on the development and updating of tools, among the tools used, there was a predominance of questionnaires and all of them evaluated aspects related to patient satisfaction with nursing care, the characteristics of the process of care, aspects of nursing interventions and aspects related to patient complaints. Although important, the tools for assessing the quality of care are still poorly studied and need further studies in the area of Nursing.